Volume 5: Manufacturing Materials and Metallurgy; Marine; Microturbines and Small Turbomachinery; Supercritical CO2 Power Cycle 2012
DOI: 10.1115/gt2012-68355
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Thermal Energy Transport to the Performance of (Semi)Floating Ring Bearing Systems for Automotive Turbochargers

Abstract: Bearing systems in engine-oil lubricated turbochargers (TCs) must operate reliably over a wide range of shaft speeds and withstanding severe axial and radial thermal gradients. An engineered thermal management of the energy flows into and out of the bearing system is paramount to ensure the components mechanical integrity and the robustness of the bearing system. The bearings, radial and thrust type, act both as a load bearing and low friction support with the lubricant carrying away a large fraction of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is well-known that unbalance plays an important role in determining both the synchronous as well as the sub-synchronous response [6,8,13]. Furthermore, when using hot gas to drive the rotor, a considerable amount of heat is conducted from the turbine to the bearing system [10], which changes the oil viscosity and thus the bearing properties [5,9]. Moreover, the non-axisymmetric air pressure distribution around the compressor wheel and the turbine wheel can cause significant radial rotor loads [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that unbalance plays an important role in determining both the synchronous as well as the sub-synchronous response [6,8,13]. Furthermore, when using hot gas to drive the rotor, a considerable amount of heat is conducted from the turbine to the bearing system [10], which changes the oil viscosity and thus the bearing properties [5,9]. Moreover, the non-axisymmetric air pressure distribution around the compressor wheel and the turbine wheel can cause significant radial rotor loads [14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12]), particularly because the complex interaction between the oil films and the rotor can lead to self-excited vibrations, resulting in excessive audible noise, wear and possibly even failure of the bearings [3]. Many recent studies on the dynamics of rotors supported by floating ring bearings have focused on automotive turbocharger applications, often with the goal to replace expensive experimental testing by numerical simulation tools [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing number of researches on heat transport in turbochargers is studied through CHT [34,35]. Individual components such as turbine, compressor and bearing housing along with full turbocharger analyses are also done using CHT [35,36]. This shows the interest of many researchers to increase the level of complexity in 3-D analysis to better model the heat transfer process.…”
Section: Three-dimensional Numerical Simulationmentioning
confidence: 99%
“…The bearing system is carefully designed to accommodate the thermal flow between the turbine and compressor. Andres et al [36] developed a thermohydrodynamic computational model of the turbocharger bearing system (floating-ring) that carefully documents the pressure and thermal profile of each component including the lubricant. Shaaban and Seume [5] showed that the heat energy transfer to the oil is 30% of the total heat transfer from the turbine.…”
Section: Coolants and Cooling Effects In Turbochargersmentioning
confidence: 99%
“…This thermal imbalance affects the amplitude of the synchronous oscillations. San Andres et al (2012) presented a thermohydrodynamic computational analysis that simulates the transfer of thermal energy in a floating annular bearing system. The paper presents the pressure and temperature fields in the inner and outer films, the radial temperatures of the ring, as well as calculating the working clearances gaps in the film and the eccentricities of the neck and ring, etc.…”
Section: Introductionmentioning
confidence: 99%